2001
DOI: 10.1038/sj.ijo.0801479
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of leptin and body weight in hyperthyroid patients after radioiodine treatment

Abstract: OBJECTIVE: Leptin regulates energy production rates and body weight, which are frequently altered in hyperthyroidism. Data on a possible interaction between leptin and thyroid hormones are controversial. We assessed leptin serum concentrations, BMI, proportional fat tissue mass and thyroid hormones in hyperthyroid patients in a long-term follow-up after radioiodine therapy. DESIGN: The study included 28 hyperthyroid patients (mean age 66 y) before and up to one y after radioiodine therapy. Leptin and thyroid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…Two studies used measurement of body composition by DEXA scans, which allows better correlations to fat measures (51,88), and found that although serum leptin levels increased during the 12-month ATD treatment of thyrotoxic patients compared with baseline and in accordance with what was found in rats (57,58,62), there was no relationship between changes in serum leptin and total fat mass.…”
Section: Human Studiesmentioning
confidence: 62%
See 3 more Smart Citations
“…Two studies used measurement of body composition by DEXA scans, which allows better correlations to fat measures (51,88), and found that although serum leptin levels increased during the 12-month ATD treatment of thyrotoxic patients compared with baseline and in accordance with what was found in rats (57,58,62), there was no relationship between changes in serum leptin and total fat mass.…”
Section: Human Studiesmentioning
confidence: 62%
“…In contrast, when two large cross-sectional groups of female patients with either pre-treatment hyperthyroidism or hyperthyroidism during treatment were compared a difference was indeed found, with low serum leptin at the time of newly diagnosed hyperthyroidism and normal serum leptin in euthyroid patients treated with ATD. Thus, an effect of ATD to increase serum leptin could be suggested, which was later confirmed in a prospective study of ATD in Graves' disease (51) and in another study of patients with nodular toxic goiter before and up to one year after radioiodine therapy (88). In both these studies (51, 88) serum leptin changes were dissociated from body weight changes as measured by BMI and from proportional or actual fat mass as measured by DEXA, indicating different rates of lean and adipose mass weight gains during normalization of thyroid function, irrespective of whether this was achieved by radioiodine therapy (88) or ATD (51).…”
Section: Human Studiesmentioning
confidence: 63%
See 2 more Smart Citations
“…There is few data available regarding the thyroid hormones and PAI-1. Studies have been focused on serum measurements, in severe hypothyroidism was found decreased PAI-1 levels [215], while in hyperthyroidism some studies show increased [113, 216,217], other decreased [83,218] as well as unaffected PAI-1 levels [219,220].…”
Section: Others Adipokinesmentioning
confidence: 99%